Islamic Educational Management and Innovation: A Comparative Study of Al-Attas and Fullan - Ahmad Qurtubi (JURNAL ISLAM NUSANTARA, 2025)
This study comparatively examines the educational management perspectives of Syed Muhammad Naquib al-Attas and Michael Fullan to formulate an integrative framework that responds to contemporary educational challenges shaped by globalisation, digital transformation, and socio-cultural change. Employing a qualitative library research design, the study analyses the primary works of both thinkers alongside relevant secondary literature, using a descriptive-comparative analysis. The findings indicate that al-Attas provides a robust moral and epistemological foundation through the concepts of Islamization of knowledge and ta’dib, positioning ethical and spiritual character formation as the core objective of education. In contrast, Fullan offers a systemic and practice-oriented model of educational innovation grounded in transformational leadership, collaboration, and continuous improvement. Despite their differing philosophical foundations, both perspectives converge on the centrality of moral purpose in sustaining meaningful and long-term educational change. The study argues that integrating al-Attas’s value-based educational philosophy with Fullan’s innovation-driven management approach enables educational institutions, particularly within Islamic contexts, to adapt to modern reforms without compromising ethical integrity, thereby fostering holistic, adaptive, and sustainable educational management models.